The Rise of Indonesia Islamic Populism in The History of Uneven and Combined Development - Oktaviano, Nandito (Indonesian Perspective, 2025)
This paper examines the rise of Islamic populism in Indonesia (2014–2019) as a far-right political movement shaped by both domestic and international forces. Existing literature—rooted in essentialist, institutionalist, or political economy frameworks—often overlooks the global dimensions of this phenomenon, remaining confined within methodological nationalism. To address this, the study employs the Uneven and Combined Development (U&CD) framework, which emphasizes the role of international structures—such as the 1998 Asian Financial Crisis, the U.S.-led War on Terror, the 2008 global financial crisis, and the rise of China—in conditioning domestic political dynamics. The paper argues that Islamic populism in Indonesia emerges from the structural effects of global capitalism and geopolitical instability, which have intensified domestic crises of representation and inequality. In this context, segments of the urban precariat have turned to exclusionary, religiously framed narratives, producing a mass movement that reflects global far-right trends: anti-elite resentment, anti-pluralism, and moral revivalism. Islamic populism in Indonesia, therefore, is not merely cultural or religious—it is a locally embedded but globally conditioned political response.